2020
DOI: 10.3389/fpsyg.2020.01614
|View full text |Cite
|
Sign up to set email alerts
|

What Impact Does Accreditation Have on Workplaces? A Qualitative Study to Explore the Perceptions of Healthcare Professionals About the Process of Accreditation

Abstract: This study seeks to explore the emerging psychosocial risks of healthcare accreditation in workplaces and understand healthcare professionals' (HCPs) perceptions of work demands and the unexpected consequences such accreditation has created for them. Methods: Twenty-seven semi-structured interviews and four focus group discussions were conducted with a variety of HCPs, including doctors, nurses, pharmacists, and allied health professionals. The study was conducted in three public hospitals and a network of pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
40
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 33 publications
8
40
0
1
Order By: Relevance
“…Our participants reported that while this was initially their experience too, patient safety and quality of care sometimes dropped after accreditation, which they attributed at least in part to increased patient numbers leading to strain on the system. Overall, our findings support the findings of Melo 14 who concluded that accreditation contributed to improvement in quality of care and patient safety, and contradict that of Alshamsi et al 15 who concluded that accreditation increased psychosocial risks resulting from increased work demands during accreditation.…”
Section: Discussionsupporting
confidence: 79%
“…Our participants reported that while this was initially their experience too, patient safety and quality of care sometimes dropped after accreditation, which they attributed at least in part to increased patient numbers leading to strain on the system. Overall, our findings support the findings of Melo 14 who concluded that accreditation contributed to improvement in quality of care and patient safety, and contradict that of Alshamsi et al 15 who concluded that accreditation increased psychosocial risks resulting from increased work demands during accreditation.…”
Section: Discussionsupporting
confidence: 79%
“…Although the participants were, hierarchically, in an influential position, the cultural resistance to introducing a major change during standards integration requires a blurring of the line between leaders and frontline workers—‘cognitive participation’. This collective engagement lends credence to previous studies that emphasised the crucial role of teamwork in implementing complex interventions [ 23 , 24 ]. However, engaging frontline workers was a strenuous task that required individualised approaches to be successful.…”
Section: Discussionsupporting
confidence: 79%
“…As reported in various contexts, these actions were challenged by financial restrictions [ 4 , 25 ], structural inadequacy and sceptical behaviour of leaders [ 6 ]. Furthermore, time constraints and co-worker stress generated certain workarounds to achieve artificial happy ends, resulting in a mismatch between the actual practice and the evidence handed to the accreditation survey team [ 24 , 26 ]. The reported stress reaffirmed the need for suitable protocols to support co-workers throughout accreditation.…”
Section: Discussionmentioning
confidence: 99%
“…The present study seeks to contribute to the existing literature in three ways. First, it attempts to build on the findings of a qualitative study by Alshamsi et al (11), which explored the psychosocial risks experienced by HCPs prior to hospital accreditation. This previous study found that HCPs experienced specific psychosocial demands prior to the hospital accreditation process, which included focusing on paperwork and attending additional training sessions or meetings.…”
Section: Introductionmentioning
confidence: 99%
“…Such demands were perceived to influence HCPs' psychological health and the continuity of patients' care. Furthermore, Alshamsi et al (11) found that HCPs sought social support, including perceived support from supervisors and colleagues, in order to reduce the effect of increased demands prior to accreditation. HCPs reported that teamwork and collaboration among individuals enhanced their engagement at work during the preparation phase of accreditation.…”
Section: Introductionmentioning
confidence: 99%